Biological Effects Of Different Mri Exposure On Single-Strand Dna Of Rabbits: An In Vivo Study - Shaheen, Ramziyah Mustafa (2024)
Modern magnetic resonance imaging (mri) systems rely on a combination of static magnetic fields (smf), gradient magnetic fields (gmf), and radiofrequency fields (rf). The potential impact of mri on dna remains a subject of debate, particularly regarding its safety. Additionally, gadolinium (gd) contrast agents, commonly used in mri, have been associated with adverse side effects such as nephrogenic systemic fibrosis. This in vivo study, conducted on 45 male rabbits, aimed to investigate the effect of different mri magnetic strengths and exposure durations on single-strand dna (ssdna). Furthermore, it explored the effects of gd and alternative contrast agents, such as magnesium chloride (mgcl₂) and zinc oxide nanoparticles (zno nps), on ssdna after mri exposure. The comet assay was used to assess dna single-strand breaks (ssb), measuring three parameters: tail length (tl), percentage of dna in the tail (% dna tail), and tail moment (tm). The study also examined hematological parameters, including white blood cells (wbc), red blood cells (rbc), hemoglobin (hb), platelets, and lymphocyte percentage (lymph%), following exposure to different mri strengths over varying durations, alongside an analysis of redox reactions.